2017
DOI: 10.1055/s-0037-1607295
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Uterine Fibroids on Infertility: A Systematic Review

Abstract: Fibroids are present in up to 27% of patients seeking reproductive assistance, and can affect fertility through cavity distortion, alteration of endometrial receptivity, and sexual function. Surgical, noninvasive, and medical approaches have been developed to manage fibroids, but evidence-based data regarding their safety and efficacy for the treatment of infertility and the effects on pregnancy outcome are limited. Myomectomy, through minimally invasive techniques, is the most evidence-based approach to fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 151 publications
2
41
0
5
Order By: Relevance
“…However, the lesions of some patients after menopause will gradually shrink and even disappear [27]. Previous studies [28][29][30] have reported that the occurrence and development of multiple uterine fibroids is associated with changes of female hormones, the concentration of estradiol in myoma tissue is significantly higher than that of normal myometrial tissue, and the concentration of estrogen receptor is also significantly higher than the surrounding area of normal myometrial tissue, while the concentration of estradiol to estrone conversion is lower, it can be seen that progesterone, progesterone and its receptors can promote the occurrence and development of uterine fibroids. Although some patients with multiple uterine fibroids have small lesions and no obvious discomfort, and it's likely to shrink or even disappear during perimenopausal period [31], more patients still have larger lesions and need surgery.…”
Section: Discussionmentioning
confidence: 97%
“…However, the lesions of some patients after menopause will gradually shrink and even disappear [27]. Previous studies [28][29][30] have reported that the occurrence and development of multiple uterine fibroids is associated with changes of female hormones, the concentration of estradiol in myoma tissue is significantly higher than that of normal myometrial tissue, and the concentration of estrogen receptor is also significantly higher than the surrounding area of normal myometrial tissue, while the concentration of estradiol to estrone conversion is lower, it can be seen that progesterone, progesterone and its receptors can promote the occurrence and development of uterine fibroids. Although some patients with multiple uterine fibroids have small lesions and no obvious discomfort, and it's likely to shrink or even disappear during perimenopausal period [31], more patients still have larger lesions and need surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Decreased serum vitamin D levels have been already confirmed in several gynecological and obstetrical pathologies, such as infertility or polycystic ovary syndrome [ 82 , 83 , 84 , 85 , 86 ]. Vitamin D is also known to affect cycle regularity through its effect on hormones such as insulin or androgens.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although surgical interventions such as myomectomy have been tried in infertile women without speci c causes, it is unclear whether the treatment of uterine broids can improve pregnancy outcomes, except for cavitydistorting myomas (submucosal, or intramural with a submucosal component). 4 The most serious concern in pregnancies after myomectomy is the risk of uterine rupture, which can result in signi cant increased morbidity and mortality for both the mother and the fetus. The incidence of uterine rupture after prior myomectomy has been reported to range from 0.2 to 3.7% in women with prior myomectomy.…”
Section: Introductionmentioning
confidence: 99%